2020
DOI: 10.1002/cche.10312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pumpkin powder addition on the rheological, sensory, and quality attributes of Taftoon bread

Abstract: Background and objectives Incorporation of dietary fibers into bread can add to nutritional composition of the finished product; however, they change the rheological properties of the dough and final product quality. The objective of the present study was to investigate the effect of pumpkin powder on the rheological properties of the dough and the quality of Taftoon bread. Findings Addition of pumpkin powder significantly increased the dough development time, dough stability, and farinograph quality number an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A higher content of phenolic substances in fortified dough samples could explain the reduction of the degree of softening [ 37 ], defined as the difference between the value recorded at the peak and the value recorded after 12 min. Moreover, quality numbers of GP5 and GP10 sharply increased compared with GP0, indicating a gain of flour ability in the production of doughs resistant to mechanical stress, as seen by Davoudi et al [ 39 ].…”
Section: Resultsmentioning
confidence: 75%
“…A higher content of phenolic substances in fortified dough samples could explain the reduction of the degree of softening [ 37 ], defined as the difference between the value recorded at the peak and the value recorded after 12 min. Moreover, quality numbers of GP5 and GP10 sharply increased compared with GP0, indicating a gain of flour ability in the production of doughs resistant to mechanical stress, as seen by Davoudi et al [ 39 ].…”
Section: Resultsmentioning
confidence: 75%
“…, 2013; Davoudi et al. , 2020). Table 1 shows the formula of bread samples prepared with wheat flour substituted with different levels (0, 5, 10, 15 and 20%) of pumpkin flour based on the dry matter content.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they linked this increase in DDT of pumpkin powder incorporated fours with increase in total fber contents of dough due to which disturbance in gluten network resisted timely development of dough. Davoudi et al [36] observed signifcant increase in DDT of composite fours from 3.9 min (control) to 4.9 min (15% pumpkin powder).…”
Section: Dough Development Time Analysis Of Added Pumpkinmentioning
confidence: 98%